The taxonomic status of Long-tailed shrews (Mammalia: genus Sorex) from Nuclear Central America - Matson, John O.; Ordóñez-Garza, Nicté (Zootaxa, 2017)
We examined 256 specimens of long-tailed shrews (Sorex) from 53 localities throughout the highlands of Nuclear Central America. We evaluate the efficacy of using three qualitative characteristics to identify populations of Sorex from Nuclear Central America: 1) the presence or the absence of a postmandibular foramen and canal; 2) relative size of U3 compared to U4; and, 3) the presence or absence of a pigmented ridge on the lingual side of each unicuspid tooth. In our data, the first character is invariable for the specimens we examined. Two species groups can be recognized based on the presence (S. salvini species group) or the absence of a postmandibular foramen and canal (S. veraepacis species group). The other two characteristics were useful, but not diagnostic. Based upon Principal Component Analysis we recognize nine species of Sorex in Nuclear Central America. Five species belong to the S. salvini species group: S. cristobalensis, S. salvini, S. sclateri, S. stizodon, and a new species from Honduras. Four species belong to the S. veraepacis species group: S. chiapensis, S. ibarrai, S. veraepacis, and a new species from western Guatemala. We also present evidence that the type locality (Cobán, Alta Verapaz, Guatemala) for S. veraepacis is not correct.